PERMAINAN TRUTH OR DARE DALAM LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA - Elviana; Warika, Lia (FISIP Universitas Malikussaleh, 2025)
This study aims to explore the game Truth or Dare in group counseling services to enhance students' self-confidence. This research uses a quantitative approach, with the chosen method being a quasi-experiment with a one-group pretest-posttest design. The sample selected consisted of 10 students using the purposive sampling technique. Data were collected using a self-confidence scale instrument. The data analysis technique used SPSS version 22 to test the hypothesis with the paired sample T-test formula, and N-Gain was used to see the improvement in students' self-confidence. The research results showed that there was a significant difference in students' self-confidence before and after the Truth or Dare game was applied. The N-Gain interpretation score indicated that there was an improvement in students' self-confidence, with a fairly effective category. It can be proven that the game Truth or Dare in group counseling services can increase students' self-confidence.